CHOICE OF DRAINING LIGATION METHOD IN THE TREATMENT OF ACUTE PARAPROCTITIS - Karabayev J.A. (Research Focus International Scientific Journal, 2024)
Severe inflammation is considered the most common pathology in urgent coloproctology. The issue of the development of fistulas of the immediate interior after the tense paraproctitis has been carried out remains unfinished at the present time. Primary radical actions in paraproctitis reduce the frequency of formation of fistulas of the immediate interior, but the presence of this method of healing surprises the muscular fibers of the locking unit of the immediate interior, which can cause anal incontinence. The significance of the draining ligature (loose set-on) in the treatment of fistulas of the immediate interior is widely popular and also well researched, which should not be noted regarding the use of this method in the treatment of strained paraproctitis.